A Pilot Study to Compare Oxidative Status between Organically and Conventionally Managed Dairy Cattle During the Transition Period1. Issue 4 (6th April 2015) - Abuelo, A; Hernández, J; Benedito, JL; Castillo, C
Contents The aim of this study was to assess the redox balance of organically managed dairy cattle (OMC; n = 40) during the transition period and to compare this with conventionally managed cattle (CMC; n = 22). Serum samples of dairy cows from two organic and one conventional farm were taken. Markers of oxidants production [reactive oxygen species] and total serum antioxidant capacity were measured in four different production stages: (i) far‐off dry (2 to 1 months before calving; 44 samples in CMC and 48 in OMC); (ii) close‐up dry (1 month until 3 days before calving; 44 CMC; 54 OMC); (iii) fresh (3 days to +1 month after calving; 44 CMC; 49 OMC); and (iv) peak of lactation (+1 to +3 months; 71 CMC; 78 OMC). Values were compared between production stages and against a metabolic baseline status (4th–5th month of pregnancy; 40 CMC; 30 OMC). Our results indicated that throughout the periparturient period, OMC had lower concentrations of reactive oxygen species, but also a lower antioxidant capacity than CMC. Indeed, when the two components of the redox balance were assessed together through the Oxidative Stress index, the values of this parameter were higher for OMC than for CMC, thereby implying a higher risk of oxidative stress. Therefore, further larger studies are needed to confirm the current observations, as organically reared animals might be exposed to a lack of antioxidants supply.